Incumbency effects and the strength of party preferences: Evidence from multiparty elections in the United Kingdom - Eggers, A; Spirling, A (University of Chicago Press, 2017)
Previous researchers have speculated that incumbency effects are larger when voters have weaker partisan preferences, but evidence for this relationship is surprisingly weak. We offer a fresh look at the question by examining the U.K.’s multiparty system. In general, the electoral value of incumbency should depend on the proportion of voters who are nearly indifferent between the parties competing for incumbency; in a multiparty system, that proportion may differ across constituencies depending on which parties are locally competitive. After first showing that U.K. voters in recent decades have stronger preferences between Conservatives and Labour than between Conservatives and Liberals, we show that incumbency effects are larger in close contests between Conservatives and Liberals than in close contests between Conservatives and Labour. By documenting how partisanship influences incumbency effects, our analysis shows that the comparative study of incumbency effects offers broader insights into electoral accountability across political systems.